2013
DOI: 10.1542/peds.2013-0887
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity and Different Types of Screen Time

Abstract: OBJECTIVE: Few prospective studies have examined separate forms of screen time in relation to adiposity. Our objective was to assess independent relations of television, electronic games (video/computer), and digital versatile disc (DVD)/videos and total screen time with change in adolescent BMI. METHODS: Using data from the 2004, 2006, and 2008 waves of the ongoing Growing up Today Study II, we assessed baseline and 2-year c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
97
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(112 citation statements)
references
References 52 publications
9
97
2
4
Order By: Relevance
“…The remaining 2 studies for screen time ) and TV viewing (Creighton et al 2011;Drenowatz et al 2013), and 1 study for computer use (Magee et al 2013) reported null findings. Among 9 of the studies, significant associations with body composition were not observed across all age groups (Hands et al 2011), sex groups (Altenburg et al 2012;Barnett et al 2010;Falbe et al 2013;Lin et al 2014), exposure measures (e.g., TV vs. movie) (Falbe et al 2013;Gilbert-Diamond et al 2014), or measures of body composition (Altenburg et al 2012;Grontved et al 2014). Primarily null findings were observed for accelerometer-derived sedentary time and breaks as well as video games and total sedentary behaviour with body composition.…”
Section: Body Compositionmentioning
confidence: 94%
See 3 more Smart Citations
“…The remaining 2 studies for screen time ) and TV viewing (Creighton et al 2011;Drenowatz et al 2013), and 1 study for computer use (Magee et al 2013) reported null findings. Among 9 of the studies, significant associations with body composition were not observed across all age groups (Hands et al 2011), sex groups (Altenburg et al 2012;Barnett et al 2010;Falbe et al 2013;Lin et al 2014), exposure measures (e.g., TV vs. movie) (Falbe et al 2013;Gilbert-Diamond et al 2014), or measures of body composition (Altenburg et al 2012;Grontved et al 2014). Primarily null findings were observed for accelerometer-derived sedentary time and breaks as well as video games and total sedentary behaviour with body composition.…”
Section: Body Compositionmentioning
confidence: 94%
“…c Dose-response gradient was observed for higher TV, sedentary time, screen time, computer with unfavourable body composition in 14 studies (Barnett et al 2010;Miller 2011;Altenburg et al 2012;Basterfield et al 2012b;Dumith et al 2012;Veitch et al 2012;Falbe et al 2013;Magee et al 2013;Mitchell et al 2013aMitchell et al , 2013bWilliams et al 2013;Berentzen et al 2014;Grontved et al 2014;Lin et al 2014).…”
Section: ) Long Accelerometer-derived Sedentary Bouts (≥5 Min)mentioning
confidence: 99%
See 2 more Smart Citations
“…assistindo televisão e a presença de televisão no quarto da criança estão diretamente relacionados com a prevalência de obesidade. [25][26][27][28][29][30][31][32] A qualidade do sono também parece ter um papel importante. Alguns estudos transversais sugerem associação entre restrição de sono e obesidade.…”
Section: Historicamente O Diagnóstico De Transtorno De Déficit De Atunclassified